Some Non-linear Parametric Resonance Oscillations Of Dumbell Satellite In Elliptical Orbit - Pandey, Mithilesh Deo; Narayan, Ashutosh (International Journal of Applied Mathematical Research, 2013)
Some non-linear parametric resonance oscillations of Dumbell satellite in elliptical orbit in the central gravitational field of force under the combined influence of Earth magnetic field ,oblateness of the Earth and some external periodic forces of general in nature has been studied.The system comprises of two charged material particles connected by a light flexible and inextensible cable ,moves with taut cable like a dumbbell satellite, in elliptical orbit around the Earth.The central gravitational field of force is the main force governing the motion and various perturbing forces influencing the system are disturbing in nature.Non-linear oscillations of dumbbell satellite about the equilibrium position in the neighbourhood of the parametric resonance  , has been studied, exploiting the asymptotic method due to Bogoliubov,Krilov and Metropoloskey ,considering ‘e’to be a small parameter .The analysis of stability of the system  has been discussed due to Poincare method.